Risk Management Analysis on Implementation Time Performance Using the House of Risk (HoR) Model in Toll Road Construction Projects - M. Iqbal Vikri Dzulfikar; Budi Susetyo (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Infrastructure development, particularly toll road construction, plays a critical role in regional transformation and economic growth, yet project delays remain a persistent issue. Specific Background: In Indonesia, approximately 38% of toll road projects experience implementation delays, as observed in the Serang–Panimbang Toll Road Section 3 project, which underwent a significant time extension. Knowledge Gap: Limited knowledge and inadequate coordination in project risk management hinder effective identification and mitigation of delay-causing factors during the implementation phase. Aims: This study aims to analyze risk factors affecting time performance and determine priority mitigation strategies using the House of Risk (HoR) model. Results: The analysis identified 18 risk events and 18 risk agents categorized into technical, managerial, environmental, and external variables, with four dominant risk agents including design inconsistency with soil data, foreign loan dependency, unprepared technical-administrative data, and land acquisition issues. Novelty: The integration of HoR Phase 1 and Phase 2 with expert validation and N-Vivo analysis provides a structured prioritization of risk agents and corresponding preventive actions. Implications: The findings support the development of targeted risk management strategies, including design validation, contractual adjustments, early document preparation, and legal verification, to reduce potential delays and improve project time performance. Highlights: Four dominant risk agents were prioritized based on Aggregate Risk Potential values. Delay causes were grouped into technical, managerial, environmental, and external categories. Preventive actions were ranked using effectiveness-to-difficulty evaluation. Keywords: Freeway, Risk Management, Risk Matrix, Risk Management Strategy